2021
DOI: 10.3390/ijerph18052332
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education, COVID-19 and Risk Factors on the Quality of Life in Patients with Type 2 Diabetes

Abstract: Background: The aim of this study was to examine the impact of education, coronavirus disease 2019 (COVID-19), and risk factors on the quality of life in patients with type 2 diabetes. Methods: A prospective study was conducted in three phases: before education, after education, and in the period of pandemic coronavirus disease 2019 (COVID-19). The subjects were diabetics on oral therapy. To determine the quality of life index, a standardized Ferrans and Powers survey questionnaire was used. Results: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
(70 reference statements)
3
14
0
5
Order By: Relevance
“…In previous research [ 29 , 30 ], the authors used five methods to predict heart failure, including logistic regression, decision tree, random forest, simple Bayesian classifier, and support vector machine (SVM). The source of the data is from the Cleveland database.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research [ 29 , 30 ], the authors used five methods to predict heart failure, including logistic regression, decision tree, random forest, simple Bayesian classifier, and support vector machine (SVM). The source of the data is from the Cleveland database.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between gender and QoL is conflicting. Two previous studies performed in Egypt [ 11 ] and Iran [ 12 ], found that women had poorer physical QoL compared to men while in a third study [ 9 ] male gender was a significant predictor of worse QoL. Likewise, it has been shown that younger Australian T2DM patients reported lower QoL compared to older ones [ 25 ].…”
Section: Discussionmentioning
confidence: 98%
“…We found that the ADDQoL AWI score was -2.2 (possible range −9 to + 3) showing a negative impact of diabetes on QoL in the current sample of T2DM patients. Likewise, several studies have shown, using different QoL and health status scales, that COVID-19 has had a negative impact on QoL in Australian [ 25 ], Croatian [ 9 ], and Danish [ 15 ] T2DM patients. In the Australian study, QoL was mainly affected for leisure activities, feelings about the future, and emotional well-being [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to assess the usability of online learning methods, and to determine their feasibility and adequacy for medical students [5] . Radu MC et al (2020)., reported that some negative aspects were reported for Covid-19 impact such as; lack of an adequate infrastructure for some students, less effective teacher-student communication and interaction, impossibility of performing practical applications, lack of socialization, lack of learning motivation, less objective examination (e.g., possibility of cheating), possibility of physical and mental health degradation (e.g., too much time spent in front of screens, installation of a sedentary lifestyle) [7,8] . Consequently, for the new academic year, effective, and efficient measures must be implemented by the management of the university to remove, as much as possible, these negative issues and to improve the performance of online educational process [7,9,10] .…”
Section: Introductionmentioning
confidence: 99%